(untitled) (Tempo e Argumento, 2023)
Epidemiological studies point to the existence of a statistical correlation between the use of psychoactive substances and deaths by suicide. Even though there is no evidence of a causal relationship, this association is based on discourses built on the logic of risk and prevention, which has a strong character of behavior control and moral evaluation. In this text, from a history of the present, we analyze how the relationship between drug use and suicide was understood. We discussed the role of the concepts of discipline, normalization, biopolitics and risk from which these behaviors come to be seen as legal and socially dangerous, placing subjects outside the register of reason and law.